Relationship Between Health Locus of Control (HLC) and Self Management in Chronic Kidney Disease Patients Undergoing Hemodialysis - Bayhakki Bayhakki; Wirdhatul Jannah Asrin; Syeptri Agiani Putri (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Chronic Kidney Disease (CKD) is a progressive and irreversible global public health problem that causes functional/structural abnormalities of the kidneys for 3 months. Hemodialysis is a kidney replacement therapy that can cause physical and psychological stress that will affect the quality of life. Aims to determine the relationship between HLC and self-management in CKD patients undergoing hemodialysis at Arifin Achmad Hospital, Riau Province. This study uses a correlational description design with a cross-sectional study approach. The results of the analysis using the Pearson test found that there was a relationship between internal HLC and partnership, problem-solving, and emotional management, but no relationship was found with self-care in CKD patients undergoing hemodialysis. There is no relationship between chance HLC and powerful others HLC with self-management indicators, namely partnership, problem-solving, self-care, and emotional management of CKD patients undergoing hemodialysis.